A comparative study of the shocking ability of electroshockers on lampam jawa,Puntius Gonionotus(Bleeker) juveniles - Azman Yusof (Fakulti Pengajian Maritim dan Sains Marin, 2011)
When a fish enters an alternating current electrical field, the initial stage of reaction observed is transverse oscillataxis. The second stage is hypnosis whereby the fish rolls onto one side. Generally, when higher voltage is applied,the fish directly exhibits hypnotic reaction. The third stage is mortality when the voltage reaches lethal threshold value.